Integrating Somatic and Germline Next-Generation Sequencing Into Routine Clinical Oncology Practice. (2021) - Hicks, J. Kevin; Howard, Rachel; Reisman, Phillip; Adashek, Jacob J.; Fields, Karen K.; Gray, Jhanelle E.; McIver, Bryan; McKee, Kelly; O'Leary, Mandy F.; Perkins, Randa M.; Robinson, Edmondo; Tandon, Ankita; et al.
Abstract : Next-generation sequencing (NGS) is rapidly expanding into routine oncology practice. Genetic variations in both the cancer and inherited genomes are informative for hereditary cancer risk, prognosis, and treatment strategies. Herein, we focus on the clinical perspective of integrating NGS results into patient care to assist with therapeutic decision making. Five key considerations are addressed for operationalization of NGS testing and application of results to patient care as follows: (1) NGS test ordering and workflow design; (2) result reporting, curation, and storage; (3) clinical consultation services that provide test interpretations and identify opportunities for molecularly guided therapy; (4) presentation of genetic information within the electronic health record; and (5) education of providers and patients. Several of these key considerations center on informatics tools that support NGS test ordering and referencing back to the results for therapeutic purposes. Clinical decision support tools embedded within the electronic health record can assist with NGS test utilization and identifying opportunities for targeted therapy including clinical trial eligibility. Challenges for project and change management in operationalizing NGS-supported, evidence-based patient care in the context of current information technology systems with appropriate clinical data standards are discussed, and solutions for overcoming barriers are provided.